The Kabbalah Centre and Spirituality of the Self - Bauer, Nicole (International Journal for the Study of New Religions, 2020)
The Kabbalah Centre is an international organization founded in the 1960sby Philip Berg in the USA. Initially founded as a group for the study ofOrthodox Judaism, through marketing strategies and de-traditionalisation,Kabbalah has been transformed, universalized, and presented as a series of"spiritual tools" for self-improvement by Berg and his successors. Throughthe Centre, religious seekers can adapt Kabbalistic elements to their personalspiritual journey, consume Kabbalistic products like Kabbalistic candles andincense or the Red String bracelets (The Kabbalah Centre, "The KabbalahOnline Store") and participate in Kabbalistic events, workshops, and seminarsonline ("Kabbalah University"). This article explores the ways in whichthe Centre aims to provide its members with a fully-equipped world of religiousexperiences, offering a form of consumable religion tailored to the selffocusedlifestyle of the postmodern seeker.